Evaluation of Three Natural Coagulant from Moringa Oleifera Seed for the Treatment of Synthetic Greywater - Carlos Peña-Guzmán; Beatriz Elena Ortiz-Gutierrez (Salehan Institute of Higher Education, 2022)
The scarcity of water has become a growing problem worldwide. The search for new sources has therefore intensified, and one of these sources is greywater. The objective of this article is to evaluate the effectiveness of three different coagulants obtained from Moringa oleiferaseed (seed husk, ground seed, and degreased) in synthetic greywater. The methodology is planned in stages; in the first stage, these seeds were selected, unsheathed, and dried in the sun for 24 hours, and the coagulant was synthesized by a 1 M NaCl solution. In the second stage, the synthetic greywater was prepared in a laboratory and included personal cleaning products and additional chemical components. Finally, a statistical test was employed to evaluate the removal of turbidity and the incidence and behavior of the turbidity, pH, alkalinity, and dissolved oxygen over seven periods and the type of coagulant. It was found that the coagulant degreased obtained the highest percentage of removal (85%) and the coagulant from seed husk had the lowest efficiency with 75%. On the other hand, it was found that parameters such as pH and dissolved oxygen depend on the type of coagulant, while conductivity and alkalinity do not depend on time or the type of coagulant. Doi: 10.28991/CEJ-2022-08-12-013 Full Text: PDF